The challenge of inter-legality / edited by Jan Klabbers, Gianluigi Palombella. - Klabbers, Jan; Palombella, Gianluigi (ASILstudies in international legal theory., 2019)
The sovereignty of states to enact and enforce laws within their jurisdictions has been recognized since the Treaty of Westphalia in 1648. There are now, however, accepted global legal norms that transcend national sovereignty and hold states accountable for not including their domestic legal regimes. This volume is the first book-length treatment to describe and explain how legal orders can be interwoven, and what to do about it. Coining the term 'inter-legality', this volume provides essays on the history, primary areas of inter-legality, the concept of jurisdiction, and normative developments prompted by inter-legality. Bringing together a wide range of contributors who stem from a variety of different academic backgrounds, this book aims to answer three questions: does inter-legality occur with some regularity? How does it affect traditional legal concepts such as 'jurisdiction' or 'legal order' or 'responsibility'? And what are the normative implications?